Cladistic analysis of Rheochlus and related genera, with description of a new species (Diptera: Chironomidae: Podonominae) - Siri, Augusto (2014)
A new species, Rheochluslatisetussp. nov., is described from male and female adults from Argentina. Emendations and illustrations of the three previously known species of Rheochlus Brundin, 1966 are provided. A cladistic analysis of the genus Rheochlus within the tribe Podonomini is presented, and the phylogenetic relationship with congeners is discussed based on adult characters